THE VOICE AND THE FILIATION - Araceli Colín (European Scientific Journal, ESJ, 2014)
Filiation according to Legendre is a structural order linked to the reproduction of the word meaning that no human being can be subject of a word of his own if he has not previously come across the incest prohibition by an instance called “Father”. Father conceived as a ternary instance culturally embedded. It is always said “on behalf of”. The possibility of reproducing the word could not be achieved without voice. Voice exceeds the word. According to Freud, it deals with a fragmented past, linked to desire, which historicizes itself in a singular matter in the analytical process. It accomplishes this through the enunciation of a mixture of ancestral voices, which inhabit the subject in an instance called Id. Freud read this historical legacy in an oscillating mode: sometimes from a ideological perspective, sometimes from a biological predisposition. As Lacan proposes, the voice is a crucial resource of generational transmission and a vehicle for filiation. In neoliberal times, the desymbolization of culture, as proposed by Dufour, has several consequences on filiation. Finally I will present three cases in which filiation is affected. Each case belongs to an ethnic group from México and Guatemala.